THE INFLUENCE OF EXCHANGE RATES AND INFLATION ON THE TRADE BALANCE OF GROUP OF EIGHT (G8) COUNTRY - Daulay, Muhammad Apis; Endraswati , Hikmah (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
The study aims to find out how much inflation and exchange rates influence trade balances in the G8 member states of France, Britain, Germany, Italy, the United States, Japan, Canada, and Russia. Starting in 2017–2022. The study uses a quantitative approach with panel data types. The analytical tool used is Eviews 13 with the panel regression method, which has three models, namely the Common Effect Model (CEM), Fixed Effect Models (FEM), and Random Effect Models (REM), selected through three model selection tests, namely the Chow Test, the Hausman Test, and the Langrange Multiplier Test. Based on the results of the study, the exchange rate and inflation variables have no impact on the trade balance sheet in the G8 countries, either partially or simultaneously, in 2017–2022.